The Use of Concept Maps in the Process of Independent Study of Educational Material in Higher Mathematics - Larisa Norik; Irina Lebedeva (Educational Challenges)
The purpose of the article is to analyze the impact of concept mapping on the level and quality of assimilation of learning material in higher mathematics in the process of independent study.